Saúde sexual de pessoas vivendo com HIV/AIDS sob a ótica da promoção da saúde. - Melo, Géssyca Cavalcante de (2015)
At the end of the last century sexual health has come to be understood as the ability of individuals to enjoy and express their sexuality, in loving dimension, of intimacy, without risks, violence and discrimination. One of the aspects that contribute to the achievement of this ability is how individuals behave front of their sexual health. This study is a qualitative research whose main objective was to analyze the behaviors related to sexual health of people living with HIV according to the Health Promotion Model of Nola Pender. Were specific objectives: 1) To identify the individual characteristics and behaviors related to sexual health of the subjects, previous to the time of the survey; 2) Describe the feelings, self-efficacy, barriers, benefits and personal influences in relation to behaviors that need to be modified; 3) Build an agreed plan of action together with the individual in relation to their behavior related to sexual health. The study included 14 people who were diagnosed with HIV/AIDS for a time like to or less than one year, over the age of 18 years. Data collection was carried out in 2014 from a script by semi-structured interviews and the Health Promotion Model was used as theoretical and methodological framework. The results showed four dimensions of behavior: 1) Non-use of condoms in all sexual relations; 2) suspension/restriction of sex life and lack of romantic relationships; 3) female submission in gender relations and 4) strengthening sex life and relationships affection. Each behavior was investigated in relation to the wishes and needs for change/maintenance, which demanded individual interventions and action planning based on the wishes expressed by seven subjects who attended the second meeting of the research. It was possible to analyze the previous behaviors related to sexual health of the participants seem to be based on the beliefs of common sense and/or one's culture, it is this opinion on the absence of satisfactory pleasure with condom use, its not practicality, understanding that HIV only is prevented with the use of this method (and therefore the decision not to relate sexually and emotionally with each other), thought that being a woman involves serve and submit to man's desires, and no guidance about other ways to conduce sexuality pleasantly. Knowledge of HIV status seems to show how a situation in which the behaviors are to be rethought so that the health of individuals and their partners is not put at risk. Yet at the same time, the wishes of behavioral change and attitude, as well as the perception of its benefits, appear permeated with fear of stigma and common lack of family and spousal support to decision-making. This study contributes to a deepening of knowledge acercada promotion of health of the person living with HIV and signals the model applied as a tool for the performance of health professionals.